Cultivation of microalgae spirulina platensis biomass using palm oil mill effluent for phycocyanin productivity and future biomass refinery attributes - Palanisamy, Karthick Murugan; Bhuyar, Prakash; M. H. A., Rahim; Govindan, Natanamurugaraj; Maniam, Gaanty Pragas (Wiley Online Library, 2023)
Palm oil mill effluent is a type of wastewater which contains a high concentration of organic nitrogen, phosphorus, and different supplement substances. These substances support and enhance the growth of microalgae. Cyanobacteria Spirulina platensis is a blue-green microalga with two phycobiliproteins as its primary constituents. Phycocyanin is a natural blue colourant used in biomedicines, cosmetics, diagnostics, treatments, and environmental protection. Chlorophyll pigment plays a significant role in photosynthesis where the photosynthetic process uses atmospheric carbon to produce starch and lipid which can eventually be converted into desirable products such as biodiesel. Therefore, in this study, Spirulina platensis was cultivated in different concentrations of diluted POME (10-50%, ) at °C room temperature, 90 μmol photon m-2 s-1, and aerated for 24 h continuously. The growth of Spirulina platensis was monitored through optical density at 680 nm for 15 days. The highest biomass yield obtained in the control medium and 30% POME medium were and  g/L, respectively. The highest phycocyanin yield obtained from the biomass harvested from 30% nutrient media was  mg and followed by  mg from control media with purified phycocyanin of  mg and  mg, respectively. The peak properties of phycocyanin such as the amide group at 1655.17 cm-1 (C=O stretching), FT-IR analysis revealed well-formed Spirulina platensis with all characteristic peaks and distinct fingerprints of phycocyanin. The ultrasound method produces the highest lipid yield (%) which consists of stearic (38.45%), palmitoleic (), and palmitic () fatty acid methyl esters. The FAME produced from the extracted lipid has the potential to be used in biodiesel applications. Since POME contains the essential nutrients which can support the growth of Spirulina platensis in the optimum environment for biomass and lipid productivity, it revealed the potential for biodiesel production.